Forensic accounting in the fraud auditing case - Simeunović, Nataša; Grubor, Gojko; Ristić, Nenad (The European Journal of Applied Economics, 2016)
This paper presents a real case of digital forensic analysis in organizational fraud auditing process investigated using two different forensic tools, namely Tableau TD3 Touch Screen Forensic Imager and Access Data FTK Imager. Fraud auditing is more of a mindset than a methodology and has different approaches from financial auditing. Fraud auditors are mostly focused on exceptions, accounting irregularities, and patterns of their conduct. Financial auditors place special emphasis on the audit trail and material misstatements. A fraud case investigation of non-cash misappropriations committed by an employee, the warehouseman, will be presented herein in order to highlight the usefulness of fraud auditing, which can reveal many forms of financial crime and can be used in both private and public sector companies. Due to the computerized accounting environment, fraud investigation requires a combination of auditing, computer crime and digital forensic investigation skills, which can be achieved through joint efforts and cooperation of both digital investigator and fraud auditor as proposed herein.